The Effect of Topical Ozonated Aloe vera on VEGF Expression and Microvascular Density in Radiation Dermatitis - Prajoko, Yan Wisnu; Silalahi, Davin Rizky Parulian; Priharsanti, Christina Hari Nawangsih; Supit, Tommy (Open access Macedonian journal of medical sciences, 2022)
BACKGROUND: Radiation dermatitis is one of the most common side effects of external radiation therapy. Ozonated Aloe vera oil is a novel topical intervention with immunomodulatory properties that have been proven to improve wound healing by promoting fibroblast proliferation and collagen synthesis. AIM: The purpose of this study was to investigate the effect of topical ozonated A. vera oil application on the vascularization aspect of wound healing in a radiation dermatitis animal model. METHODS: Thirty-six adult male Sprague Dawley rats were randomized into six groups of equal size (n = 6/group): two control and four intervention groups: Positive control (C1) rats were not given any therapy, and comparative control (C2) rats were given topical hydrocortisone cream 2.5%. Subjects in the P1 group were given non-ozonated A. vera therapy, P2 group was given 300 mg/mL ozonated A. vera, P3 group was given 600 mg/mL ozonated A. vera, and P4 was given 1200 mg/mL ozonated A. vera therapy. Subject termination and histopathological analyses of vascular endothelial growth factor (VEGF) and microvascular density were carried out after 7 treatment days. RESULTS: Based on Weidner microvascular density scoring system, the least microvascular density was observed in C2, P3, and P4 (2.0 ± 0.0), followed by P1 (2.1 ± 0.1), P2 (2.9 ± 1.5), and C1 (3.0 ± 0.7). Based on immunoreactive immunoreactive score (IRS) VEGF scoring system, the lowest expression of VEGF was observed in group P3 (4.1 ± 1.1), followed by P4 (4.3 ± 0.8), C2 (4.3 ± 1.3), P1 (5.1 ± 1.0), P2 (5.4 ± 0.6), and C1 (6.5 ±1.0). There was a strong positive correlation of VEGF and microvascular density. CONCLUSION: Topical application of ozonated A. vera to the radiated skin of Sprague Dawley rats reduced VEGF expression and microvascular density. This anti-inflammatory effect may suggest its potential clinical application.